ANALISIS KUALITAS PELAYANAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG - Nora Sembadra Mahardhika; Endang Larasati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Ownership of birth certificate is very important since it is a form of someone’s identity which will be used as the basis to obtain other public services. Based on the data from Department of Population and Civil Registration of Semarang in 2004-2014, there are still 127.369 childerns have not had birth. Thus, this research aims to analyze the quality of service of the birth certificate and to know factors influence it in Department of Population and Civil Registration of Semarang. The research method used was descriptive qualitative while the election informants technique was purposive sampling. The researcher collected the data through interviews, observation, and study documentation. The result of this research indicates that, there are three of five quality dimensions service that are not qualified. Those are tangible, reliability, and responsiveness. It is seen from the quantity of infrastructure that is still inadequate and less carefully preserved, the procedure of birth certificate that is not socialized well, the customer service that does not serve well, the lack of awareness of the birth certificate applicants for their rights, and there is no customer care available yet. Therefore, Department of Population and Civil Registration of Semarang has to give more good response to all the service birth certificate with responsive, reliable, right, and accurate. Also, the applicants should be more active and aware of the importance of the birth certificate. They could also take part in the service of birth certificate in Department of Population and Civil Registration of Semarang.